2023
DOI: 10.1111/jsr.13949
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐existing sleep problems as a predictor of post‐acute sequelae of COVID‐19

Abstract: SummarySeveral months after COVID‐19 many individuals still report persisting symptoms, the so‐called ‘post‐COVID‐19 syndrome’. An immunological dysfunction is one of the main pathophysiological hypotheses. As sleep is central to the functioning of the immune system, we investigated whether self‐reported pre‐existing sleep disturbance might be an independent risk factor for the development of post‐COVID‐19 syndrome. A total of 11,710 participants of a cross‐sectional survey (all tested positive for severe acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(77 reference statements)
2
3
0
Order By: Relevance
“…Specifically we find a mean difference of 0 • 6/0 • 58 in mean well-being score and a mean difference of 0 • 76/0 • 73 between P S and P C/NC individuals. This is in line with recent findings, where individuals reporting persistent symptoms also reported poorer mental health in comparison to a control group [40], as well as a study reporting disturbed sleep as an important risk factor for PCC [41].…”
Section: Discussionsupporting
confidence: 93%
“…Specifically we find a mean difference of 0 • 6/0 • 58 in mean well-being score and a mean difference of 0 • 76/0 • 73 between P S and P C/NC individuals. This is in line with recent findings, where individuals reporting persistent symptoms also reported poorer mental health in comparison to a control group [40], as well as a study reporting disturbed sleep as an important risk factor for PCC [41].…”
Section: Discussionsupporting
confidence: 93%
“…33 Our sleep quality measure combined the effects of both sleep efficiency and sleep duration, but exploratory analyses suggested that low and inconsistent sleep efficiency-which can reflect a range of sleep disturbances, such as increased sleep latency and fragmented sleep-was driving the relationship observed. This is in line with other studies, which have found increased risk of long COVID associated with pre-infection sleep disturbances, [9][10][11] whereas results on sleep duration are inconsistent 9,10 and do not always consider the simultaneous effect of sleep efficiency. 35 Together, these findings suggest short sleep duration, on its own, is unlikely to substantially increase the risk of long COVID; instead, the focus should be on ensuring consistently good-quality sleep to aid recovery from future infections.…”
Section: Discussionsupporting
confidence: 90%
“…8 Sleep quality has also been implicated in the development of long COVID among those infected, with studies finding a wide range of sleeprelated measures such as sleep quality, sleep duration, and pre-existing sleep disorders predicting the development of long COVID. [9][10][11][12] This research, however, is still in its infancy, with studies presenting conflicting findings on the associations with different sleep measures; 9,10 heterogeneity between study definitions of long COVID, ranging between symptoms lasting 4 weeks 9 and 6 months; 11 and reliance on retrospectively reported pre-infection sleep data. 11 More research is therefore needed to build our understanding of this relationship.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a report of 1,581 adults from the United Kingdom, poor-quality sleep in the month before initial SARS-CoV-2 infection increased the risk of long COVID (odds ratio [OR] 3.5), as did average sleep quality (OR 2.5) (19). In a similar study, pre-existing sleep disturbances were an independent predictor of subsequent probable post-COVID-19 syndrome (20). Sleep disturbances were reported by more than half of the participants, were usually a new symptom, and were independent of a mood disorder in most cases.…”
Section: Similar Symptoms Of Fm and Me/cfs In Long Covid Syndromementioning
confidence: 95%